In Vitro Scolicidal Activity of the Sesquiterpenes Isofuranodiene, α-Bisabolol and Farnesol on Echinococcus granulosus Protoscoleces - Youssefi, Mohammad Reza; Nikpay, Ali; Hassanpour, Niloufar; Mirzapour, Aida; Tabari, Parisa Saleh; Pavela, Roman; Maggi, Filippo; Petrelli, Riccardo (Molecules (Basel, Switzerland), 2020)
Cystic echinococcosis (CE) remains an important challenge both in humans and animals. There is no safe and suitable remedy for CE, so the discovery of new compounds with promising scolicidal effects, particularly from herbal sources, is of great importance for therapeutic uses in the treatment and prevention of CE reappearance. Sesquiterpenes are C15 organic compounds made up of three isoprene units and mostly occurring as fragrant components of essential oils. They are of economic importance for the cosmetic and pharmaceutical industry, and recently attracted the attention of the scientific community for their remarkable parasiticidal properties. In the present study, we have focused on three known sesquiterpenes, isofuranodiene (IFD), α-bisabolol (BSB), and farnesol (FOH), as important phytoconstituents of the essential oils of wild celery (Smyrnium olusatrum), chamomile (Matricaria chamomilla), and acacia farnese (Vachellia farnesiana), respectively. Protoscoleces were recovered from fertile hydatid cysts and were exposed to different concentrations of the three tested compounds for different exposure times. The viability of protoscoleces was confirmed by 0.1% eosin staining. Results of scolicidal activity evaluations showed that IFD possessed the best effect against Echinococcus granulosus protoscoleces (LC50 and LC90 values of 8.87 and 25.48 µg/mL, respectively), followed by BSB (LC50 of 103.2 µg/mL) and FOH (LC50 of 113.68 µg/mL). The overall toxicity of IFD differed significantly from those of FOH and BSB, while there was no significant difference in toxicity between the latter compounds (p > 0.05). The present study showed that IFD seems to be a promising scolicidal agent and can be further tested to become a candidate for CE treatment.
Keywords: protoscolex; monocyklické seskviterpeny; antiparazitární látky; LD50; isofuranodiene; Monocyclic Sesquiterpenes; furany; Sesquiterpenes; seskviterpeny; α-bisabolol; Animals; Antiparasitic Agents; zvířata; farnesol; Farnesol; Lethal Dose 50; Echinococcus granulosus; cystic echinococcosis; Furans